Spondylodiscitis as the only clinical manifestation of the onset of psoriatic spondyloarthritis - V. Bruzzese (Reumatismo, 2011)
Psoriatic arthritis falls within the family of seronegative spondyloarthritis given that the involvement of the spine, whether in combination with peripheral arthritis or not, is one of the most common clinical fi ndings of the disease. Symptomatological polymorphism of the disease, however, still includes several clinical subsets ranging from peripheral arthritis, mono-, oligo- and polyarticular, to enthesitis and dactylitis, all the way to crippling arthritis. Despite the frequent